1990
DOI: 10.1128/iai.58.9.2785-2791.1990
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of rat T helper cell clones specific for Bacteroides gingivalis antigen

Abstract: During the past several years, much interest has been directed towards delineating and characterizing different subsets of T helper (Th) cells in order to understand their roles in immune processes. In this study, we report the generation of antigen-specific rat Th cell clones and their characterization in terms of phenotype, function, and lymphokine production. The clones were derived by culturing purified splenic T cells from rats immunized with the pathogen Bacteroides gingivalis with equivalent numbers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The cytokine pattern observed, i.e., no IL-2 and large quantities of IFN-y, is in keeping with findings described by other investigators. Thus, Katz et al (17) have shown that splenic murine T-helper cell clones specific for Bacteroides gingivalis exhibited low IL-2 activity and high IFN--y activity. Similarly, Autenrieth et al (3) reported the isolation of splenic murine T-cell clones specific for Yersinia enterocolitica, producing small or nondetectable quantities of IL-2 and considerable quantities of IFN-y (500 mU/ml), comparable to the amounts of IFN--y detected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The cytokine pattern observed, i.e., no IL-2 and large quantities of IFN-y, is in keeping with findings described by other investigators. Thus, Katz et al (17) have shown that splenic murine T-helper cell clones specific for Bacteroides gingivalis exhibited low IL-2 activity and high IFN--y activity. Similarly, Autenrieth et al (3) reported the isolation of splenic murine T-cell clones specific for Yersinia enterocolitica, producing small or nondetectable quantities of IL-2 and considerable quantities of IFN-y (500 mU/ml), comparable to the amounts of IFN--y detected in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous animaJ models have been developed which have been extremely valuable in providing information important to our understanding of virulence properties of P. gingivalis (1,3,4,10,11,13,17,18,21,22). For instance.…”
mentioning
confidence: 99%
“…Along with several other oral bacteria, Porphyromonas gingivalis, Actinobacillus actinomycetemcomitans, and Prevotella intermedia have been implicated in the initiation and progression of different forms of this disease (18). The immunopathogenic mechanism involved in periodontitis is not understood, although the interaction between bacterial antigens and T lymphocytes in inflamed oral lesions has been suggested to be of importance in the pathogenesis of the disease in human (12,39) and experimental rat (16,44,50) models. In addition to bacterial antigens, autoantigens have also been considered to play a role in the pathogenesis of periodontitis (1,4).…”
mentioning
confidence: 99%